Health risks, emergency preparedness and Norwegian-Russian cooperation on Svalbard. A systematic review - Wæhler, Turid Austin; Ingebrigtsen, Tor (International Journal of Circumpolar Health, 2022)
This is the first systematic review to explore health risks on Svalbard. We have analysed data retrieved from 18 articles that met eligibility criteria and present a mixed-methods quantitative and qualitative narrative synthesis. Norwegian and Russian inhabitants on Svalbard were compared with the respective mainland populations, and we found no evidence of an increased risk for or prevalence of diseases. The rate of injuries caused by snowmobile accidents were significantly higher, but this was outweighed by a correspondingly lower rate of other injuries. A small unique risk for injuries inflicted by polar bears was confirmed. We identified knowledge gaps concerning how health care and emergency preparedness are organised.